Ferroelectric glass ceramics based on the bismuth germanate system - Pengpat K. (2014)
Glasses have been formed from the BiO1.5-GeO2-BO 1.5 and BiO1.5-GeO2-TeO2 systems and glass ceramics produced by controlled devitrification. The ferroelectric phase, orthorhombic Bi2GeO5, crystallises in all of the borate glasses studied and is the dominant phase for the 60BiO1.5:20GeO 2:20BO1.5 composition. The glass forming region of the BiO1.5-GeO2-TeO2 system is quite narrow and, whilst Bi2GeO5 could be formed along with Bi 4TeO8 at low TeO2 contents, this was replaced by Bi4(GeO4)3 at higher concentrations. On increasing the temperature, the Bi2GeO5 devitrification in the borate containing glass ceramics changes from spherulitic to surface crystallisation which can be used to produce oriented growth. Such Bi 2GeO2 glass ceramics are ferroelectric at room temperature with TC=407°C. The polarisation Ps=0-14 Clm 2 is comparable with that of BaTiO3 ceramic but a high voltage is required for poling. The preferred orientation of the surface crystallisation in this glass ceramic is perpendicular to the Bi 2GeO5 (311) planes but a-axis orientation may be preferable, in order to enhance the electrical properties.